Multiple Sluicing in English?. (30th April 2013) - Lasnik, Howard
Abstract Several cases have been discovered where syntactic violations seem to be "repaired" by sluicing. One such case is repair of island violations, first observed by Ross (1969). Another is situations in which a normally obligatory movement fails to apply and the derivation is seemingly salvaged by ellipsis. Another potential instance of repair by ellipsis involves cases where an element moves although it should not have, but the violation is seemingly ameliorated by sluicing. That type is the focus of this article. In particular, English does not generally allow multiple wh‐movement, but under some circumstances it seems to allow multiple sluicing. I explore the properties of this apparent multiple sluicing in English and argue instead for a rightward movement account of the second wh‐expression, especially based on "Right Roof" effects and on a constraint on P‐stranding.